Ecology Of Pranajiwa Medicinal Plants (Euchresta horsfieldii (lesch.) benn.) In Bali And Lombok: (A Review) - Rafika Rizki (International Journal of Ecophysiology, 2022)
This article is a review of the ecology of pranajiwa medicinal plants in Bali and Lombok. In this article, the author discusses the characteristics of pranajiwa’s original habitat in Bali and Lombok, the abundance, habitat vegetation, and distribution of pranajiwa, as well as environmental factors that affect pranajiwa’s habitat. The purpose of this article is to identify the characteristics of pranajiwa’s natural habitat in Bali and Lombok to ensure long-term preservation and sustainable use of pranajiwa